Globalization, the State and the Labor Process - H. Friedland, William (The International Journal of Sociology of Agriculture and Food, 2021)
After defining key terms, state and labor processes in pre-globalization capitalism are examined and the nation-state is found to be the key constraining element in state imperatives of accumulation, legitimation, and mediation of class conflict. In the globalization period, the labor processes in four commodity systems - automobiles, petroleum, sugar, and bananas - are compared. The main changes in labor processes in agricullure during globalization involve the elaboration of the division of labor and combined and uneven development. Both are examined in the context of several agricultural commodities. It is concluded that globalization creates greater degrees of freedom from the constraint of nation-states for capital to install new labor processes.